2014
DOI: 10.4085/1062-6050-49.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Outcomes of Web-Based Modules Designed to Enhance Athletic Trainers' Knowledge of Evidence-Based Practice

Abstract: Although the EBP Web-based modules were successful at enhancing knowledge among ATs, translation of knowledge into the classroom and clinical practice remains limited. Researchers should aim to identify effective strategies to help ATs implement EBP concepts into didactic education and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Recently, researchers 24 have revealed that whereas ATs perceive they have retained knowledge gained from the Web-based modules, they have not shifted that knowledge to their daily practices in patient care. For this reason, it is necessary to seek strategies that will be most effective in bridging the gap between knowledge and practice.…”
mentioning
confidence: 99%
“…Recently, researchers 24 have revealed that whereas ATs perceive they have retained knowledge gained from the Web-based modules, they have not shifted that knowledge to their daily practices in patient care. For this reason, it is necessary to seek strategies that will be most effective in bridging the gap between knowledge and practice.…”
mentioning
confidence: 99%
“…15,16 Data analysis within the CQR framework includes a four-part process: (1) identify code domains, (2) extract core ideas from each 15,16 A detailed description of the CQR data analysis process has been previously published. 15,16,18 The frequency counts for each category were divided into four components: (a) general, (b) typical, (c) variant, (d) rare. 16 For this qualitative study, a category was considered general if it applied to all or all but one participant cases, typical if it applied to seven or more cases, variant if it applied to less than seven cases, or rare if the data only related to one or two participant cases.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The CQR approach has been previously established in athletic training research. [17][18][19][20] This study was approved by the A.T. Still University Institutional Review Board and email consent was obtained from each participant, along with verbal consent prior to each participant's interview.…”
mentioning
confidence: 99%
“…Previous research [10][11][12][13][14] in athletic training shows that foundational knowledge of EBP concepts is low. Stand-alone workshops, journal clubs, and clinically integrated teaching improve knowledge of EBP and critical appraisal in medicine, 15 whereas web-based modules increase foundational EBP knowledge in athletic trainers (ATs).…”
Section: Athletic Trainers' Current Knowledge and Envisioned Use Of Fmentioning
confidence: 99%
“…Stand-alone workshops, journal clubs, and clinically integrated teaching improve knowledge of EBP and critical appraisal in medicine, 15 whereas web-based modules increase foundational EBP knowledge in athletic trainers (ATs). 12,14 In addition to knowledge, information has been previously disseminated regarding barriers to use and implementation of EBP. [16][17][18][19][20][21] Although valuable in content, these previous studies were conducted before the implementation of the BOC requirement regarding EBP continuing education.…”
Section: Athletic Trainers' Current Knowledge and Envisioned Use Of Fmentioning
confidence: 99%